Genetic Diversity and Phylogenetic Analysis of Citrus tristeza virus Isolates from Turkey - Gözde Erkiş-Güngör; Bayram Çevik (Advances in Virology, 2019)
The presence of Citrus tristeza virus (CTV) in Turkey has been known since the 1960s and the virus was detected in all citrus growing regions of the country. Even though serological and biological characteristics of CTV have been studied since the 1980s, molecular characteristics of CTV isolates have not been studied to date in Turkey. In this study, molecular characteristics of 15 CTV isolates collected from different citrus growing regions of Turkey were determined by amplification, cloning, and sequencing of their major coat protein (CP) genes. The sequence analysis showed that the CP genes were highly conserved among Turkish isolates. However, isolates from different regions showed more genetic variation than isolates from the same region. Turkish isolates were clustered into three phylogenetic groups showing no association with geographical origins, host, or symptoms induced in indicator plants. Phylogenetic analysis of Turkish isolates with isolates from different citrus growing regions of the world including well-characterized type isolates of previously established strain specific groups revealed that some Turkish isolates were closely related to severe quick decline or stem pitting isolates. The results demonstrated that although CTV isolates from Turkey are considered biologically mild, majority of them contain severe components potentially causing quick decline or stem pitting.